STUDIES ON THE BIOLOGY OF STREPTOCOCCUS : III. AGGLUTINATION AND ABSORPTION OF AGGLUTININ WITH STREPTOCOCCUS SCARLATINÆ. - Stevens, Franklin A. (The Rockefeller University Press, 1924)
1. Strains of hemolytic streptococci from cases of scarlet fever occurring in New York, San Francisco, Chicago, Baltimore, and Copenhagen, Denmark, all interagglutinate with immune sera prepared with these strains. 2. Sera prepared with these strains do not agglutinate pyogenic streptococci or strains isolated from cases of septic sore throat. 3. The strains obtained from the throats of patients from an epidemic of scarlet fever and the strain from the milk responsible for this epidemic fall into the scarlatinal group according to these agglutination tests. 4. Absorption tests can be carried out with these strains and sera under proper conditions. 5. A group of hemolytic streptococci biologically distinct from streptococci from other sources than scarlet fever is constantly associated with scarlatina. They constitute a group of closely related streptococci which may be identified by agglutination tests.